Penerapan Media Pembelajaran Multimedia Interaktif Untuk Meningkatkan Kemampuan Mengenal Huruf Pada Anak Kelompok B RA AL Munawarah - Marlina Sungke; Sitriah Salim Utina; Sitti Rahmawati Talango (Universitas Muhammadiyah Ponorogo, 2026)
Early childhood education is a very important stage in developing children's full potential without neglecting their physical and psychological conditions. This research uses a classroom action research method with observation and documentation data collection techniques. However, initial observations at RA Al Munawarah show that the letter recognition skills of children in group B are still in the early stages of development, with children finding it difficult to distinguish between letters that are similar in shape and sound. This condition is influenced by teaching methods that are still conventional and do not utilize innovative learning media that are appropriate for early childhood characteristics. Therefore, this study aims to determine whether the application of interactive multimedia learning media can improve the ability to recognize letters in group B children at RA Al Munawarah. Based on the research results, there was an increase in the ability to recognize letters in children from the pre-cycle with an average percentage result of 44.10%, then after the action was carried out in cycle I with an average percentage result of 71.96%, after being carried out in cycle II with an average percentage result of 94.46%. Therefore, the application of interactive multimedia learning media can improve children's ability to recognize letters because it integrates elements of text, images, sound, animation, and interaction which can create an interesting, fun, and meaningful learning atmosphere for children.